2002
DOI: 10.1148/radiol.2252011025
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Localization of Small Pulmonary Lesions with a Short Hook Wire and Suture System: Experience with 168 Procedures

Abstract: This system with a flexible suture for preoperative localization has a high success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
137
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 25 publications
7
137
0
Order By: Relevance
“…Studies have showed that pneumothorax and pulmonary hemorrhage, with an incidence of 32.1-68% and 10.3-36%, respectively, in preoperative hook wire placement (22,29,30). Ichinose and colleagues represented similar result, of 500 lesions underwent CT-guided localization, pneumothorax was observed in 49% of the patients immediately after location, only 4.6% require intervention (22), much higher than other study (apply double-thorn hook wire) reported (18.6% and 24.4%) (23).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have showed that pneumothorax and pulmonary hemorrhage, with an incidence of 32.1-68% and 10.3-36%, respectively, in preoperative hook wire placement (22,29,30). Ichinose and colleagues represented similar result, of 500 lesions underwent CT-guided localization, pneumothorax was observed in 49% of the patients immediately after location, only 4.6% require intervention (22), much higher than other study (apply double-thorn hook wire) reported (18.6% and 24.4%) (23).…”
Section: Discussionmentioning
confidence: 99%
“…The same group published their results in 2002 for 168 patients, with a success rate of 97.6% (4 dislodgements). Procedure time was reported as 25-28 min, and although most patients [110] went to the OR within 1 h, 38 patients waited from 4-14 h between the hookwire insertion and resection (26). Using this system, Miyoshi et al attempted to determine risk factors for dislodgement, but found none that had a significant impact.…”
Section: Discussionmentioning
confidence: 99%
“…of VATS pulmonary resection, and our rate of 98.3% was comparable to that in previous reports. [2][3][4][5] Preoperative lipiodol marking of impalpable pulmonary nodules has several advantages over other marking methods such as metallic coil, [6][7][8][9] hook wire, [10][11][12][13][14] dye, [15][16][17] and barium. [18][19][20] First, it is possible to determine the proper central surgical cut lines because lipiodol can be injected adjacent to targeted lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative localization appears to resolve the former issue, and a number of small nodule localization techniques aimed at guiding VATS resection have been developed. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Although there are many techniques for preoperative localization of pulmonary lesions, CT-guided lipiodol marking may be the most appropriate method for impalpable pulmonary lesions for several reasons. We describe the procedure and assess the usefulness of the CT-guided lipiodol marking technique based on our experiences.…”
Section: Introductionmentioning
confidence: 99%